Excellent online friendships: an Aristotelian defense of social media - Elder, Alexis (Ethics and Information Technology, 2014)
I defend social media's potential to support Aristotelian virtue friendship against a variety of objections. I begin with Aristotle's claim that the foundation of the best friendships is a shared life. Friends share the distinctively human and valuable components of their lives, especially reasoning together by sharing conversation and thoughts, and communal engagement in valued activities. Although some have charged that shared living is not possible between friends who interact through digital social media, I argue that social media preserves the relevantly human and valuable portions of life, especially reasoning, play, and exchange of ideas. I then consider several criticisms of social media's potential to host friendships, and refute or weaken the force of these objections, using this conception of a distinctively human shared life. I conclude that we should use the shared life to evaluate features of social media and norms for users' conduct.
Keywords: Aristotle; Data privacy; Friendship; Information technology; Privacy; Shared activity; Social media; Social networking (online); Social sciences; Valuable component; dept.phi

On the possibility of quantum informational structural realism - Bynum, Terrell Ward (Minds and Machines, 2014)
In The Philosophy of Information, Luciano Floridi presents an ontological theory of Being qua Being, which he calls "Informational Structural Realism", a theory which applies, he says, to every possible world. He identifies primordial information ("dedomena") as the foundation of any structure in any possible world. The present essay examines Floridi's defense of that theory, as well as his refutation of "Digital Ontology" (which some people might confuse with his own). Then, using Floridi's ontology as a starting point, the present essay adds quantum features to dedomena, yielding an ontological theory for our own universe, Quantum Informational Structural Realism, which provides a metaphysical interpretation of key quantum phenomena, and diminishes the "weirdness" or "spookiness" of quantum mechanics. © 2013 The Author(s).
Keywords: Dedomena; Digital ontology; Primordial qubit; Quantum information; Structural realism; dept.phi

Association and asylum - Cavallero, Eric (Philosophical Studies, 2014)
Keywords: dept.phi

Zhuangzi on friendship and death - Elder, Alexis (Southern Journal of Philosophy, 2014)
Zhuangzi suggests that death is a transformation that we commonly and mistakenly think means the end of someone but really just marks a new phase of existence. This metaphysical thesis is presented at several points in the text as an explanation of distinctively Daoist responses to death and loss. Some (such as Wong 2006) take a Daoist response to death, as presented by Zhuangzi, to indicate dual perspectives on friendship and death. But I argue that the metaphysical view sketched above is consistent with a unified perspective, allowing the Daoist to enjoy deep friendships without risking some potential for grief typically associated with strong attachment. However, it leaves the Daoist best suited to friendships with those who endorse the same metaphysics. Furthermore, while the grief associated with the death of a friend is somewhat mitigated, the Daoist has reason to mourn even given this thesis. © 2014 The University of Memphis.
Keywords: dept.phi

Situating the early schelling in the later positive philosophy - Harry, Chelsea C (Comparative and Continental Philosophy, 2014)
This is a translation of the second chapter of F.W.J. Schelling's Abhandlungen zur Erlaüterung des Idealismus der Wissenschaftslehre (1796-1797). It is preceded by a brief introduction in which I situate the chapter within Schelling's oeuvre and suggest that it is not only an early articulation of Schellingian Naturphilosophie, but also prescient, anticipating Schelling's later positive philosophy. © W. S. Maney & Son Ltd 2014.
Keywords: Naturphilosophie; Negative philosophy; Positive philosophy; Schelling; dept.phi

Helping students to see for themselves that ethics matters - Jagger, Suzy; Volkman, Richard (The International Journal of Management Education, 2014)
Business ethics education is experiencing a renaissance as recurring corporate scandals and malpractice over the last decade have ensured that most universities now see the subject as an important and necessary component of any business degree course. As well as integrating professional ethics into their curriculum, Business Schools are also developing standalone ethics courses, showing that they take seriously their responsibility to help prepare the next generation of managers to improve business' track record of transparency, accountability and sustainable development. However what are the learning approaches that will help to bring about real improvements in business ethics learning at university? This paper argues that a holistic approach to ethics teaching is needed, in which students are encouraged to develop ethical knowledge and skills within their personal value systems. In this way ethics does not become something apart but integrated into one's terms of reference. The paper discusses a particular pedagogic approach designed to develop a student's 'critical consciousness' using a student-led learning method in which students actively engage with important concepts and discuss the issues amongst themselves within an environment where they can speak freely. Qualitative interviews with a selection of undergraduates on the compulsory first year professional ethics module provide insight into the impact of the method on attitudes and behaviours. © 2013 Elsevier Ltd.
Keywords: Business ethics; Moral sensitivity; Teaching business ethics; Transformational learning; Values and integrity; Virtue ethics; dept.phi